Developing inclusive education through a collaborative transatlantic approach - Johnson, Jean; Dyer, Jonny; Lockyer, Ben (Συνέδρια της Ελληνικής Επιστημονικής Ένωσης Τεχνολογιών Πληροφορίας & Επικοινωνιών στην Εκπαίδευση, 2023)
Growing numbers of young people are dropping out of formal education although there is little research available about disaffection from learning by teenagers. What is available focuses on those in schools rather than those who rarely if ever attend. Using an inductive paradigm and participatory action research, this paper looks at a successful ICT based online community of practice for teenagers excluded from formal education and asks whether this model can be adapted in a transatlantic context. It asks whether two distinct groups can form a collaborative learning community by creating an opportunity for them to learn as separate cultural groups as well as collaborating in distinct curriculum areas. Preliminary findings suggest that where online learning for this disadvantaged group of young people is built around the concept of social networking and a constructivist approach to curriculum is used, engagement in learning occurs.